ITO - free thermal free OPV fabrications - Li, Hong. (2009)
As the amount of fossil fuel is continuously decreasing and the burning of this fuel brings severe environmental problems, harvesting solar energy using photovoltaic technologies have been continuously attracting attention. In recent years, the organic photovoltaics (OPVs) have become even popular due to their cost-effective features. One of the techniques used to improve performance of OPV is thermal annealing, which limits OPV fabrication on flexible substrates with low heat resistance. On the other hand, indium tin oxide (ITO) which is scarce in amount and costly has been the material of choice for the anode of OPVs.